Ribavirin Enhances IFN-α Signalling and MxA Expression: A Novel Immune Modulation Mechanism during Treatment of HCV - STEVENSON, NIGEL; KEOGH, CATHERINE; HEGARTY, JOHN; O'FARRELLY, CLIONA; BOURKE, NOLLAIG (My University, 2011)
The nucleoside analogue Ribavirin significantly increases patient response to IFN-? treatment of HCV, by directly inhibiting viral replication. Recent studies indicate that Ribavirin also regulates immunity and we propose that Ribavirin enhances specific interferon sensitive gene (ISG) expression by amplifying the IFN-?-JAK/STAT pathway. We found that IFN-?-induced STAT1 and STAT3 phosphorylation was increased in hepatocytes co-treated with Ribavirin and IFN-?, compared to IFN-? alone. Ribavirin specifically enhanced IFN-? induced mRNA and protein of the anti-viral mediator MxA, which co-localised with HCV core protein. These novel findings indicate for the first time that Ribavirin, in addition to its viral incorporation, also enhances IFN-?-JAK/STAT signalling, leading to a novel MxA-mediated immuno-modulatory mechanism that may enhance IFN-? anti-viral activity against HCV.
PUBLISHED
Keywords: Immunology; Hepatitis C Virus (HCV); Genes & Society; Immunology, Inflammation & Infection